Criminal or administrative responsibility of legal persons? Some contributions concerning the Legislative Decree N° 30424 - Carrión Díaz, Juan Elías (2018)
The responsibility of legal persons in Criminal Law has a recent treatment in Peru. In this article, the author analyzes the criminal and administrative responsibility of legal persons taking into account the Legislative Decree N° 30424. According to his evaluation, he explains that legal persons do not comply with some elements drafting the offence.